Investigations on the Restorations of Erased Engraved Marks on Steel Surfaces - Zaili, Mohd Azlan Mohd (Universiti Sains Malaysia, 2006)
Restoration of erased engraved marks is considered difficult compared to the restoration of stamped marks, as the deformation occurring to the metal due to the engraving is minimal. Hence a series of experiments was designed to test the sensitivity and efficacy of different metallographic reagents that are traditionally used on steel surfaces to reveal erased stamped marks. The experiments consisted of preparing several steel plates with engraving marks and erasing these engravings marks to different levels down to the depth of engraving. Then some selected reagents were used on them using swabbing technique to restore the erased engraved marks. The results have shown that the reagents of Sg cupric sulphate (CuS04), 60 ml hydrochloric acid (HCl), 30 ml concentrated ammonium solution (NH30H), 60 ml water and also Sg cupric chloride (CuC}z), 50 ml hydrochloric acid (HCl), 30 ml water (H20) are quite sensitive and effective in the recovery process of erased engraved marks. It is also noted during these experiments that the disturbance caused to the steel surfaces occurring to original engraving has penetrated just through 0.04 mm below the bottom of the engraved marks.